Health Care Seeking Behaviour Of Community And Tb Patients, And Capability Of Nonformal Health Services Provider In Tanjung Bintang Subdistrict, Indonesia - Nurul Islamy (Fakultas Kedokteran Universitas Lampung, 2012)
In Lampung province, Indonesia, the case detection rate (CDR) has not reached the national target of 70%. This suggests that tuberculosis (TB) case finding is insufficient. In Tanjung Bintang subdistrict (Lampung) the CDR was only 27.8% in 2007. This study aimed to identify the reasons for the low CDR in Tanjung Bintang subdistrict. In an explorative study design we assessed health care seeking behavior of community members who were selected by systematic random sampling. We also assessed health care seeking behavior of all TB patients that were registered between 2001 and 2007 in the subdistrict public health center (PHC). To assess the diagnostic capacity of non-formal Health Service Providers (HSP), we interviewed all HSP in the subdistrict. Data analyzed descriptively using Epi-info. Community members mentioned that they would first visit midwives (31%), paramedics (18.8%) and subhealth centers (18.8%) for mild symptoms. Most TB patients (97.5%) reported that they initially visited a nonformal HSP for their symptoms. Most (85.2%) nonformal HSP have poor knowledge about general TB especially for symptoms and 45.8% of them refer TB patients to a private practioner or private hospital rather than to the PHC (54.2%). Community members and TB patients frequently seek care with nonformal HSP. Since most nonformal HSP have poor knowledge of TB and do not refer TB patients to the PHC many TB patients may remain not reported. The fact that patients do not seek health care at PHC and nonformal HSP are not capable of diagnosing TB can both explain the low CDR in Tanjung Bintang subdistrict